(untitled) (Heritage, 2024)
This paper stands out striking structural features on morphological plan which illustrates not finished progressive situation in the speech of Plemetina concerning the predominance of dialectal features of Kosovo-Resava or Prizren–South Morava zones of speech. It has been displayed on the range of analytic innovations and degree of preservation of synthetic structures in the speech of Plemetina, all by giving relations to neighboring local languages and zones. According to system of declension of nouns, the learning local speech is inclined to north and north east conditions on the area of Kosovo dialect nevertheless it has not been exempted from mediocrity. In the domain of pronouns and adjectives word change, as well as in comparison of adjectives, there have been parallel analytic and synthetic principles and their combination. The generalization of Balkan innovations in verb system to the greatest extent includes the formation of future forms.